Management of chronic anterior uveitis relapses: efficacy of oral phospholipidic curcumin treatment. Long-term follow-up - Pia Allegri; Antonio Mastromarino; Piergiorgio Neri (Clinical Ophthalmology, 2010)
Pia Allegri1, Antonio Mastromarino1, Piergiorgio Neri21Uveitis Center, Ophthalmological Department of Lavagna Hospital, Genova, Italy; 2Uveitis Unit, The Eye Clinic, Azienda Ospedaliero-Universitaria, Ospedali Riuniti di Ancona, Ancona, ItalyAbstract: Curcumin has been successfully applied to treat inflammatory conditions in experimental research and in clinical trials. The purpose of our study is to evaluate the efficacy of an adjunctive-to-traditional treatment with Norflo tablets (curcumin-phosphatidylcholine complex; Meriva) administered twice a day in recurrent anterior uveitis of different etiologies. The study group consisted of 106 patients who completed a 12-month follow-up therapeutic period. We divided the patients into three main groups of different uveitis origin: group 1 (autoimmune uveitis), group 2 (herpetic uveitis), and group 3 (different etiologies of uveitis). The primary end point of our work was the evaluation of relapses frequency in all treated patients, before and after Norflo treatment, followed by the number of relapse in the three etiological groups. Wilcoxon signed-rank test showed a P < 0.001 in all groups. The secondary end points were the evaluation of relapse severity and of the overall quality of life. The results showed that Norflo was well tolerated and could reduce eye discomfort symptoms and signs after a few weeks of treatment in more than 80% of patients. In conclusion, our study is the first to report the potential therapeutic role of curcumin and its efficacy in eye relapsing diseases, such as anterior uveitis, and points out other promising curcumin-related benefits in eye inflammatory and degenerative conditions, such as dry eye, maculopathy, glaucoma, and diabetic retinopathy.Keywords: curcumin, anterior recurrent uveitis, phosphatidylcholine-bound-curcumin (Meriva)